A strategic concept for an effective Philippine Coast Guard role in monitoring, control, and surveillance system for Philippine fisheries - Gayosa, Daniel Inri S. (Miagao, Iloilo University of the Philippines in the Visayas, 2001)
Illegal fishers are threatening The Philippine fishery. To address these threats and to properly manage The Philippine fisheries MCS-CPRR system was conceived. Economic circumstances, cultural norms, and individual personalities and values of managers are factors that affect compliance to MCS measures. Being the country's premier maritime enforcement agency, the PCG needs to address these factors and formulate strategy to enhance compliance. An effective enforcement strategy has seven components. It starts with (1) the creation of regulation that is enforceable. To (2) identify stakeholders and set priorities, the PCG should interact with stakeholders and identify the impact of its function. To (3) promote compliance, strentghening of partnership, publicizing accomplishments, and operating intelligently, efficiently and effectively are essential. (4) Violation and compliance can be monitored by sharing important information,leverage existing and new technologies, properly execution and documentation of patrol operation and gathering of accurate data. (5) To respond to violations, it s mportant to properly plan action, train and deploy personnel, prevent encroachment of illegal fishers, built-up of sufficient asset and equipment, prompt imposition of sanctions, and by involving private sector. (6) To clarifying roles and responsibilities, close working relationship wth other agencies and role identification is important. (7) To evaluate and designate responsibilities, it is important to develop expertise in evaluation, performance planning and execution, conduct of special studies for MCS and the development of the PCG to a knowledgeable, discipline, professional maritime law enforcement force.
Special Problem (MMA) -- Miagao, Iloilo : University of the Philippines in the Visayas, 2001.